2018
DOI: 10.1016/j.bjid.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility of quadrivalent versus trivalent influenza vaccine in Brazil – comparison of outcomes from different static model types

Abstract: All three models predicted a cost per quality-adjusted life year gained for quadrivalent versus trivalent influenza vaccine in the range of R$19,257 (FLORENCE) to R$22,768 (FLORA) with the best available data in Brazil (Appendix A).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
0
12
0
4
Order By: Relevance
“…2 ). Details regarding the model used have been previously published [ 13 ] and its validity (structural and conceptual) [ 14 ] assessed by an internal panel of cross-functional experts (functions including, but not limited to, medical, epidemiology, and statistics).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…2 ). Details regarding the model used have been previously published [ 13 ] and its validity (structural and conceptual) [ 14 ] assessed by an internal panel of cross-functional experts (functions including, but not limited to, medical, epidemiology, and statistics).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Public health authorities may not be able to predict which B lineages will be circulating and which one will be dominant, particularly in a country crossing different climatic area like Brazil. A previous costeffectiveness analysis already showed that switching from TIV to QIV would be a cost-effective strategy in Brazil (13). However, this study did neither consider societal costs, nor could account for indirect effect of vaccination.…”
Section: Discussionmentioning
confidence: 94%
“…They contain two influenza A strains (A/H1N1 and A/H3N2) as well as two B lineages (B Victoria and B Yamagata), while previous trivalent influenza vaccines (TIV) only contained one B lineage. They have been recommended and shown their improved effectiveness as well as their cost-effectiveness in replacing TIV in several countries (10)(11)(12)(13). In Brazil, the public health and economic benefits of QIV have been demonstrated using various methodologies, but all relying on a "static model" approach, hence not accounting for the indirect impact of vaccination (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They contain two influenza A strains (A/H1N1 and A/H3N2) as well as two B lineages (B Victoria and B Yamagata), while previous trivalent influenza vaccines (TIV) only contained one B lineage. They have been recommended and shown their improved effectiveness as well as their cost-effectiveness in replacing TIV in several countries [ 10 13 ]. In Brazil, the public health and economic benefits of QIV have been demonstrated using various methodologies, but all relying on a “static model” approach, hence not accounting for the indirect impact of vaccination [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%